RIFM fragrance ingredient safety assessment, 1-(3, 3-dimethylcyclohexyl)pent-4-en-1-one, CAS Registry Number 56973-87-6. (November 2016) - Api, A.M.; Belsito, D.; Bhatia, S.; Bruze, M.; Calow, P.; Dagli, M.L.; Dekant, W.; Fryer, A.D.; Kromidas, L.; La Cava, S.; Lalko, J.F.; LapczynskI, A.; et al.
Highlights: 1-(3, 3-Dimethylcyclohexyl)pent-4-en-1-one safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. All endpoints were cleared using data on the target material and/or TTC.